2020
DOI: 10.15421/022089
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of strains of lactic acid bacteria isolated from Carpathian cheese

Abstract: A promising area for improving probiotics is the search for new sources of strains and the development of complex preparations which would include different types of bacterial cultures that complement each other. Sources of selection may be traditional dairy products, in particular, cheeses made from raw milk. Wild strains can be endowed with antibacterial properties. The antagonistic action of lactic acid bacteria (LAB) has long attracted the attention of researchers and scientists. The aim of the study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Lactococcus lactis IMAU32258, L. garvieae JB2826472, Enterococcus durans FMA8, E. faecium L3-23, E. faecium IMAU9421 were isolated from Carpathian cheese as cell-free supernatant (CFS) without any addition of hydrogen peroxide or adjusted pH value. The antagonistic activity of the bacteriocins LAB against pathogenic was studied by Musiy et al (2020). They found that E. durans FMA8 had the highest activity against S. typhimurium PCM 2182, followed by L. monocytogenes PCM 2191, E. coli PCM 2208, and S. aureus PCM 458.…”
Section: Bacteriocins Produced By Lab Isolated From Cheesesmentioning
confidence: 99%
“…Lactococcus lactis IMAU32258, L. garvieae JB2826472, Enterococcus durans FMA8, E. faecium L3-23, E. faecium IMAU9421 were isolated from Carpathian cheese as cell-free supernatant (CFS) without any addition of hydrogen peroxide or adjusted pH value. The antagonistic activity of the bacteriocins LAB against pathogenic was studied by Musiy et al (2020). They found that E. durans FMA8 had the highest activity against S. typhimurium PCM 2182, followed by L. monocytogenes PCM 2191, E. coli PCM 2208, and S. aureus PCM 458.…”
Section: Bacteriocins Produced By Lab Isolated From Cheesesmentioning
confidence: 99%
“…Їхня мікробіальна композиція формувалася упродовж багатьох століть (Uroic et al, 2014), вона відповідальна за надання специфічних органолептичних і фізико-хімічних властивостей молочним продуктам (Liong & Shah, 2005;Zhong et al, 2016), в тому числі й бринзі (Slyvka et al, 2017;Tsisaryk et al, 2017). Також з-посеред представників мікрофлори природних біоценозів є культури, наділені функціональними властивостями (Coconnier et al, 1993;Charteris et al, 1998;Choi & Chang, 2015;Kumari et al, 2016;Ahn et al, 2017;Choi et al, 2018;Musiy et al, 2020;.…”
Section: вступunclassified